Photocyclization of 1,4-Naphthaquinone with β-Alanine - Abd El Latif, F.M.; Khalafalla, A.K.; Badar, M.Z.A.; Dopp, D. (Asian Journal of Chemistry, 2010)
1,2,3,4-Tetrahydro benz[g] quinoline-4,5,10-trione was isolated in quantitative yield via photocycloaddition of β-alanine to 1,4-naphthaquinone in ethanol using high pressure mercury lamp as well as sunlight irradiation.